Study on Stress Disturbed Mechanism and Supporting Method of Weakly Cemented Roadway near Chambers - Wei Zhang (Complexity)
After excavation of the weakly cemented roadway adjacent to the chambers, deformation characteristics such as roof subsidence, roadway extrusion, and floor heave appear, showing the characteristics of large deformation of surrounding rock, long deformation duration, and serious damage, which are not conducive to guaranteeing safety mining. Based on the technical means of the rock mechanical property test, mineral composition analysis, in situ stress test, and surrounding rock deformation monitoring of 2# coal roadway in Hongqingliang coal mine, a numerical simulation study on the influence of surrounding rock stress on adjacent chamber groups was carried out. The physical and mechanical properties of the weakly cemented rock were obtained, the stress distribution law of the 2# coal roadway was mastered, the deformation characteristics of the surrounding rock of the weakly cemented roadway were obtained, and the deformation and failure mechanism of the weakly cemented roadway adjacent to the chambers were revealed. The relationship between the regional stress increment of the chambers and the failure range of the surrounding rock of the roadway is revealed, establishing a mechanical model of allowable deformation + stress release + controlled form with U-shaped steel as the main structure. The roadway support countermeasures were given and applied in engineering practice.